2019
DOI: 10.1039/c9ra07826f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of centrifugally spun prepared poly(lactic acid)/gelatin/ciprofloxacin nanofibers for antimicrobial wound dressing

Abstract: Centrifugal spinning is a novel technology for producing ultrafine fibers in high yield with diameters ranging from micro to nanometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Other parameters (voltage, distance from the collector, needle diameter) influence the fiber morphology to a lesser degree. In recent papers, Forcespinning ® technology has been used to produce nano-and microsized PLA fibers and the optimal processing conditions were determined [45,46]. Thus, it was shown that both polymer concentration and rotation speed influence the PLA fiber morphology, with the average fiber diameter decreasing with an increase in rotation speed.…”
Section: Morphologymentioning
confidence: 99%
“…Other parameters (voltage, distance from the collector, needle diameter) influence the fiber morphology to a lesser degree. In recent papers, Forcespinning ® technology has been used to produce nano-and microsized PLA fibers and the optimal processing conditions were determined [45,46]. Thus, it was shown that both polymer concentration and rotation speed influence the PLA fiber morphology, with the average fiber diameter decreasing with an increase in rotation speed.…”
Section: Morphologymentioning
confidence: 99%
“…First, we recorded two peaks at 1086 and 1182 cm −1 (derived from the C O C stretching vibration) in the spectra of all membranes. The absorption peak at 1752 cm −1 recorded in both membranes was due to C O stretching vibrations [ 30 ]. We assigned the peaks at 1548 and 1650 cm −1 in the spectrum of PLLA/gelatine membrane to the amide II band N H symmetric deformation absorption peak and amide I band C O stretching vibration absorption peak of gelatine.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro drug release experiments under physiological conditions showed a sustained release of ciprofloxacin from the hybrid nanofibers with a high zone of inhibition in vitro against S. aureus and E. coli . The pristine nanofiber did not display any significant antimicrobial activity [ 87 ].…”
Section: Gelatin-based Hybrid Wound Dressingsmentioning
confidence: 99%